Management of patella fractures with different modalities - Ramu, Chokkarapu; K., Rajender; B., Anjaneyulu; B., Keertana; P., Shanmuga Raju (International Journal of Research in Orthopaedics, 2019)
Background: Patella fracture is quite a common injury for all ages of patients, constituting approximately 1% of all skeletal injuries. Patella is the largest sesamoid bone in the body. The aim of study was to assess the functional outcome of patella fractures treated with modified tension band wiring using K wires and cannulated cancellous screws with tension band construct. Methods: This study was a prospective clinical study to be conducted at the Department of Orthopaedic Surgery, Chalameda Anand Rao Institute of Medical Sciences, Karimnagar from October 2016 to November 2018. Total, 20 patients with transverse patellar fractures were studied and divided into 2 groups according to the surgical technique: 10 patients were in the MKTB group and 10 patients in the CSTB group. Results: Total 20 patella fractures were included in this study. The Bostman’s score of ROM, pain, atrophy of quadriceps femoris, and effusion were all higher in the CSTB group than in the MKTB group. Conclusions: We conclude that compared with the MKTB technique, CSTB fixation is an effective surgical procedure for treatment of displaced transverse patellar fractures.